2017
DOI: 10.1002/ece3.3449
|View full text |Cite
|
Sign up to set email alerts
|

Genome comparisons indicate recent transfer ofwRi‐likeWolbachiabetween sister speciesDrosophila suzukiiandD. subpulchrella

Abstract: Wolbachia endosymbionts may be acquired by horizontal transfer, by introgression through hybridization between closely related species, or by cladogenic retention during speciation. All three modes of acquisition have been demonstrated, but their relative frequency is largely unknown. Drosophila suzukii and its sister species D. subpulchrella harbor Wolbachia, denoted wSuz and wSpc, very closely related to wRi, identified in California populations of D. simulans. However, these variants differ in their induced… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 72 publications
(195 reference statements)
1
33
0
Order By: Relevance
“…The split WOSuziC sequenced was concatenated to allow for a more robust phylogenetic reconstruction ( fig. 4 ), but it is in fact disrupted by a transposase ( Conner et al. 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…The split WOSuziC sequenced was concatenated to allow for a more robust phylogenetic reconstruction ( fig. 4 ), but it is in fact disrupted by a transposase ( Conner et al. 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…To assess the quality of these three draft assemblies, we used BUSCO v.3.0.0 to search for homologs of the near-universal, singlecopy genes in the BUSCO proteobacteria database (Simão et al 2015). For comparison, we followed Conner et al (2017) and performed the same search on the reference genomes for wMel (Wu et al 2004), wRi (Klasson et al 2009), wAu (Sutton et al 2014), and wHa and wNo (Ellegaard et al 2013) (Table S3).…”
Section: Genomic Datamentioning
confidence: 99%
“…Such cladogenic acquisition seems to be the rule for the obligate Wolbachia found in filarial nematodes (Bandi et al 1998); and there are also examples in at least two insect clades, Nasonia wasps (Raychoudhury et al 2009) and Nomada bees (Gerth and Bleidorn 2016). In contrast, infections can be relatively young and acquired through introgressive or horizontal transfer (Raychoudhury et al 2009;Schuler et al 2016;Conner et al 2017;Turelli et al 2018). Comparisons of host nuclear and mitochondrial genomes with the associated Wolbachia genomes enable discrimination among cladogenic, introgressive, and horizontal acquisition (Raychoudhury et al 2009;Turelli et al 2018; see Supplemental Material, Figure S1).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Despite this observation, several studies have reported animals as acceptors in this process. Genomic sections of the endosymbiotic bacteria Wolbachia pipientis have been found in fruit flies and wasps (Conner et al, 2017;Dunning Hotopp et al, 2007). Anecdotally, HGT in the opposite direction was also observed because genomic regions of the mosquito Aedes aegypti were detected in W. pipientis.…”
mentioning
confidence: 99%